Применение генетического алгоритма для решения краевых задач - Вакал, Л.П. (Проблемы управления и информатики, 2015)
Запропоновано генетичний алгоритм для розв’язання крайових задач для звичайних диференціальних рівнянь другого порядку і крайових задач для еліптичних рівнянь. Наведено результати чисельних експериментів розв’язання лінійних і нелінійних задач. Знайдені розв'язки подаються в аналітичній формі. Досліджено вплив параметрів генетичного алгоритму на точність розв’язків і швидкість збіжності. A genetic algorithm for solving boundary value problems for second-order ordinary differential equations and boundary value problems for elliptic equations is proposed. Results of numerical experiments for solving linear and nonlinear problems are presented. The obtained solutions are presented in the analytical form. The influence of genetic algorithm parameters on the solutions accuracy and convergence rate is investigated.